Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Is there a simpler method to this solve this equation


$$(x-2y+1)\text dx+(4x-3y-6)\text dy=0$$


$$\frac{\text dy}{\text dx}=\frac{2y-x-1}{4x-3y-6}$$

$$\frac{\text d Y}{ \text d X}=\frac{2(Y+k)-(X+h)-1}{4(X+h)-3(Y+k)-6}$$

$$\frac{\text d Y}{ \text d X}=\frac{2Y-X+(2k-h-1)}{4X-3Y+(4h-3k-6)}$$


$$2k-h-1=0\qquad4h-3k-6=0$$ $$h=2k-1\qquad 4(2k-1)-3k-6=0$$ $$5k-10=0\qquad k=2\qquad h=2(2)-1\qquad h=3$$ $$y=Y+2\qquad\qquad x=X+3$$ $$Y=y-2\qquad\qquad X=x-3$$


$$\frac{\text d Y}{\text d X}=\frac{2Y-X}{4X-3Y}=\frac{2\left(\frac{Y}{X}\right)-1}{4-3\left(\frac{Y}{X}\right)}$$

$$\left(\frac{Y}{X}\right)=V\qquad Y=VX$$

$$\frac{\text d Y}{\text d X}=X\frac{\text d V}{\text d X}+V$$

$$X\frac{\text d V}{\text d X}+V=\frac{2V-1}{4-3V}$$

$$X\frac{\text d V}{\text d X}=\frac{2V-1}{4-3V}-V$$

$$X\frac{\text d V}{\text d X}=\frac{2V-1}{4-3V}-V\left(\frac{4-3V}{4-3V}\right)$$

$$X\frac{\text d V}{\text d X}=\frac{3V^2-2V-1}{4-3V}$$

$$\frac{\text dX}{X}=\frac{4-3V}{3V^2-2V-1}\text dV$$

$$\int\frac{\text dX}{X}=\int\frac{4-3V}{3V^2-2V-1}\text dV$$

$$\ln X=\int\frac{4-3V}{3V^2-2V-1}\text dV$$


$$3V^2-2V-1=(V-1) \overline {\bigg)3V^2-2V-1}$$

$$\qquad3V+1$$$$=(V-1) \overline {\bigg)3V^2-2V-1}$$$$\quad\qquad3V^2-3V$$$$\qquad\qquad\qquad\qquad V-1$$$$\qquad\qquad\qquad\qquad \underline{V-1}$$$$\qquad\qquad\qquad\qquad 0$$

$$3V^2-2V-1=(V-1)(3V+1)$$

$$\frac{4-3V}{3V^2-2V-1}=\frac{4-3V}{(V-1)(3V+1)}=\frac{\alpha}{(V-1)}+\frac{\beta }{(3V+1)}=\frac{(3V+1)\alpha+(V-1)\beta}{(V-1)(3V+1)}$$

$$4-3V=(3V+1)\alpha+(V-1)\beta$$ $$4-3V=3V\alpha+\alpha +V\beta-\beta$$ $$4-3V=\alpha-\beta+(3\alpha +\beta)V$$ $$4=\alpha-\beta$$ $$-3=3\alpha+\beta$$ $$4+\beta=\alpha$$ $$-3=3(4+\beta)+\beta$$ $$-15=4\beta$$ $$\beta=\frac{-15}{4}$$ $$4=\alpha-\left(\frac{-15}{4}\right)$$ $$\alpha=4-\frac{15}{4}=\frac{16}{4}-\frac{15}{4}=\frac14$$


$$\ln X=\int\frac{1/4}{V-1}-\frac{15/4}{3V+1}\text d V$$

$$\ln X=\frac{1}{4}\int\frac{1}{V-1}-\frac{15}{3V+1}\text d V$$

$$4\ln X=\ln(V-1)-5\ln(3V+1)+c$$

$$\ln \left(X^4\right)=\ln\left({\frac{(V-1)}{(3V+1)^5}}\right)+c$$

$$X^4=\frac{V-1}{(3V+1)^5}\times e^c$$

$$(3V+1)^5X^4=e^c(V-1)$$

$$(3V+1)^5X^5=AX(V-1)$$

$$(3XV+X)^5=A(XV-X)$$

$$(3X\tfrac{Y}{X}+X)^5=A(X\tfrac{Y}{X}-X)$$

$$(3Y+X)^5=A(Y-X)$$

$$(3(y-2)+(x-3))^5=A((y-2)-(x-3))$$

$$(3y+x-9)^5=A(y-x+1)$$

share|improve this question
1  
+1 for using $\TeX$ to write out long division :-) –  joriki Nov 5 '12 at 10:00
    
Do you see any defects in my answer? I got -2 because of this answer and don't know why?? Thanks for your time. + –  B. S. Jan 4 '13 at 6:37
    
As far as I can tell your response hasen't added anything, you have outlined the method I have used above. I am looking for a different method that could potential simplify the calculation. –  Elements in Space Jan 4 '13 at 6:55
add comment

1 Answer

I just know that when we have a first differential equation as $$f(a_1x+b_1y+c_1)dx+g(a_2x+b_2y+c_2)dy=0$$ then if two lines $$a_1x+b_1y+c_1=0\\a_2x+b_2y+c_2=0 \;\;^*$$ are not parallel $(\frac{a_1}{a_2}\neq\frac{b_1}{b_2})$ so we can use the new change of variable as you also did above $$x=X+\alpha\\y=Y+\beta$$ in which $(\alpha,\beta)$ is the solution of above system of equations$^{*}$. I think you can find the point of intersection of lines first and then omit the constants in your equation (for example +1 and -6) temporary. After solving the homogeneous equation, as you did above, do as following: $$X\to x-\alpha\\Y\to y-\beta$$

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.